About Research in the Arts: a lover’s discourse - Pérez Royo (Universidad de Zaragoza – Zaragoza, Spain), Victoria (Revista Brasileira de Estudos da Presença, 2022)
This paper is the result of an exercise of experimental re-writing and analogical thinking which had as an aim to open a new perspective on research in the arts. In terms of method, the different figures of love in Barthes’ A Lover’s Discourse are forced to talk about the relationship of researcher and object of study. This analogy allows us to find quality parameters based on a scale of values different to the hegemonic ones in the academy (productivity, competitiveness, innovation). These new parameters might constitute a solid ontological basis to build a new politics of artistic research in the academy that allow a radical reconsideration of processes of artistic research.